Engineering theory and practice: wisdom of thinking - Cywiński, Zbigniew (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper considers the mutual relationship and cooperation between engineering theory and practice in the development of the professional performance of engineers. In this paper, theory is understood as the ability of creative thinking - the spiritus movens (moving spirit) of any reasonable human activity, and that of the engineer's in particular. Therefore, high standards of general education preceding the university schooling, and at the university itself, should be of much concern for the engineering students, educators, and practitioners - in order to develop intellectually mature humans-engineers. The nontechnical demands placed upon the engineer require more than pure technical capabilities. The author wishes to present the development and the state-of-the-art of his own judgment in that matter.
Keywords: praktyka inżynierska; edukacja; kształcenie uniwersyteckie; engineering theory; engineering practice; education